Chemotherapy-free treatment for acute promyelocytic leukemia: the pediatric view of a revolutionary tale - Masetti, Riccardo; Muratore, Edoardo; Leardini, Davide; Baccelli, Francesco; Pession, Andrea; Prete, Arcangelo; Locatelli, Franco (Frontiers in Oncology, 2023)
The addition of all-trans retinoic acid (ATRA) to the standard anthracycline-base chemotherapy has revolutionized the treatment of acute promyelocytic leukemia (APL) over the last decades, becoming a model for precision medicine. The protocols based on the combination of ATRA and chemotherapy allowed obtaining excellent response rates both for children and adults. However, the persistence of anthracycline chemotherapy as a backbone was a matter of concern for both acute and long-term complications. Efforts in reducing anthracycline cumulative dose or even eliminating anthracycline have been pursued in more recent pediatric protocols thanks to the introduction of arsenic trioxide (ATO). The impressive results of the ATRA/ATO combinations led to the introduction of protocols completely chemotherapy-free for standard-risk adult patients as the standard of care, whereas pediatric chemo-free protocols are still currently under evaluation. In this Review, we will critically retrace the history of this unique revolution in precision medicine, discussing the peculiar advantages for pediatric patients with APL.